The language of leadership narratives : a social practice perspective - Clifton, Jonathan; Schnurr, Stephanie, 1975-; Mieroop, Dorien Van De (London ; New York : Routledge, Taylor and Francis Group, 2020)
"Fascination with leadership and its relation to world events seems to be ever growing and leadership narratives are a key element in which leader identities are constructed. Contemporary research into leadership tends to recycle the same old myths of the heroic white male leader. By looking at stories told by leaders in Australasia, Asia, North America, the Middle East and Africa, this book explores different aspects of leadership narratives. The Language of Leadership Narratives brings linguistics and leadership research together, showcasing different analytical and methodological approaches and enabling a more critical approach. Each chapter focuses on a specific area of leadership research from dark leadership to gendered leadership. This book introduces the advantages of analysing leadership narratives as social practice and discusses some of the main themes in contemporary leadership research. This volume is key reading for scholars and students of linguistics, communication studies and business studies, and for those working in business and intercultural communication in the workplace"--
Includes bibliographical references (pages 181-197) and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Leadership; Communication in management